A CNN-Based Hand Gesture and Facial Recognition Interface for Contactless Human-Computer Interaction - SR, Prasad; K, Charan; Makkithaya, Ghanashyama K P, Keerthana M S; P, Larine Theresa (International Journal of Computer Sciences and Engineering, 2025)
Traditional input devices such as the mouse and keyboard, while precise and widely adopted, present limitations in terms of physical strain, accessibility, and adaptability to diverse user needs. To address these challenges, this study proposes a comprehensive, gesture-driven human-computer interaction (HCI) system that integrates four critical components. First, a combination of advanced computer vision algorithms and libraries was employed for real-time skin detection, hand tracking, feature extraction, and gesture-based cursor control. Convolutional Neural Networks (CNNs) were central to the gesture recognition pipeline, enabling accurate and adaptive interpretation of visual input. Second, a secure authentication and authorization mechanism was developed using CNN-based facial recognition in conjunction with hand tracking, ensuring personalized and protected user access. Third, the system features a responsive graphical user interface (GUI), designed using Python’s Tkinter framework, which supports customizable gesture-to-command mappings and provides real-time user feedback. Finally, the system's adaptability and robustness were validated across multiple computing environments. This work contributes to the evolving field of contactless interaction by presenting an integrated framework that emphasizes usability, security, and interoperability, with potential applications in assistive technologies, smart environments, and touch-free computing systems